A multi-center, prospective, single-arm, open label, 13-month intervention study of a plant-based, high energy and protein enteral tube feed in home enterally tube fed patients - Hubbard, Gary P.; Griffen, Corbin; Capener, Rebecca; Wyer, Nicky; Martin, Rebecca; Raif, Rachel; Green, Lisa; Sutcliffe, Sheryl; Michaels, Elizabeth; Dube, Yvonne; Bates, Johanna; Bidgood, Alina; et al. (Frontiers in Nutrition, 2025)
IntroductionThere is an emerging need for plant-based options for home enteral tube feeding (HETF) patients, however their long-term efficacy and safety needs to be established.MethodsForty-one HETF patients (age: 51 years (SD 23); range 19–84 years; 54% male) participated in a multi-center, prospective, single-arm, open label, 13-month intervention study of a plant-based, high energy, high protein (2 kcaL/mL and 10 g protein/100 mL) enteral tube feed with or without added fiber (1.5 g/100 mL). Seventeen patients continued on the plant-based feed beyond day 28 (28 D) with a 6- and 13-month follow-up (6 M and 13 M). Outcomes included gastrointestinal tolerance (GI), anthropometrics, muscle strength and function (handgrip strength, 30-s chair stand test (30SCST)), dietary intake, total daily feed volume and time for feeding, and safety.ResultsCompared to patient’s baseline feeding regimen, patients using the plant-based feed reported: greater absence of GI symptoms at all time points (+7–12%, p ≤ 0.04); a reduced incidence and intensity of GI symptoms: bloating, burping at 28 D (p < 0.05) and constipation, flatulence at 13 M (p < 0.05); improved physical function between 6 M and 13 M (+2 30SCST repetitions, p = 0.02), with maintenance of body weight, calf circumference and handgrip strength; total protein intake increased at all time points (+0.2–0.3 g/kg/day, p < 0.05); and total daily feed volume (−225 to −264 mL/day, p < 0.05) and estimated time for pump feeding (−2 h/day, p < 0.05) reduced at all time points.DiscussionThis longitudinal study highlights that a plant-based (vegan-suitable) high energy, high protein enteral tube feed has good tolerance in HETF patients, positive long-term effects on protein intake and potential benefits on physical function.